Cytokines and acute phase proteins associated with acute swine influenza infection in pigs - Barbé, Filip (Vet J, 2011)
This study set out to investigate the cytokines and acute phase proteins (APPs) associated with the acute stages of experimentally-induced swine influenza virus (SIV) infection in 3-week-old, colostrum-deprived, caesarean-derived piglets. The piglets were inoculated intratracheally with 10(7.5) 50% egg infective dose [EID(50)] Swine/Belgium/1/98 (H1N1) SIV and were euthanased at time-points between 0 and 120 h post-inoculation (PI). Broncho-alveolar lavage fluid (BALF), lung homogenates and sera were examined for inflammatory mediators by bioassay or ELISA. Interferon (IFN)-α, interleukin (IL)-6, IL-1 and tumour necrosis factor (TNF)-α peaked in BALF 24–30 h PI, when virus titres and the severity of clinical signs were maximal. Whereas IFN-γ and IL-12, but not IL-18, increased in tandem in BALF, serum cytokine concentrations were either undetectable or were up to 100-fold lower. The APP C-reactive protein (CRP) and haptoglobin peaked 24 h later than the cytokines and reached higher levels in serum than in BALF. In contrast, lipopolysaccharide (LPS)-binding protein (LBP) only increased in BALF. Lung virus titres tightly correlated with BALF IFN-α, IL-6, IL-1, TNF-α, IFN-γ and IL-12, as well as with serum IL-6, IFN-α and IFN-γ. Signs of disease correlated with the same cytokines in BALF and serum, as well as with BALF LBP and serum CRP. The findings suggest that IFN-γ and IL-12 play a role in the pathogenesis of SIV and that APPs are induced by cytokines. This influenza infection model may have value in assessing the therapeutic potential of cytokine antagonists.